Clinical Studies of Statins in Asthma and COPD - C. Thomson, Neil (Current Molecular Pharmacology, 2017)
Immunomodulatory effects of statins in vitro and in experimental models of asthma and COPD could potentially be relevant to the treatment of chronic airway diseases. This article provides an overview of the evidence from the key clinical studies on the effects of statins on clinical outcomes and inflammatory biomarkers in asthma and COPD. Future directions for clinical studies of statins in asthma and COPD are discussed. A small number of randomized controlled trials (RCTs) in adults with mild to moderate asthma suggest that short-term statin treatment does not improve lung function or symptom control, except for a possible improvement in quality of life and symptoms in smokers with asthma. Several observation studies report that statin use in asthma is associated with a reduced risk of asthma-related emergency department visits, oral corticosteroid dispensing or hospital admissions. Statins treatment in asthma may have modest local anti-inflammatory effects in the airways. There is a need for a large RCT examining the effects of statins on reducing exacerbations, particularly in severe asthma. In COPD, observational studies suggest that statin use is associated with reduced morbidity and/or mortality, whereas a large RCT concluded that simvastatin did not reduce exacerbations in patients with COPD that had no cardiovascular indication for statin treatment. It is possible that a subgroup of COPD patients with cardiovascular indications for statins and/or systemic inflammation may obtain clinical benefit from statin treatment. Understanding the immunomodulatory effects of statins in asthma and COPD may lead to the development of novel targeted interventions.
Keywords: statin